2013
DOI: 10.1021/pr400476a
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Tegument-Exposed Proteins of Female and Male Schistosoma japonicum Worms

Abstract: The interplay between sexes is a prerequisite for female growth, reproductive maturation, and egg production, and the basis of schistosome pathopoiesis and propagation. The tegument is in direct contact with the host environment and its surface membranes are particularly crucial for schistosome survival in the definitive host. In this study, a streptavidin-biotin affinity purification technique combined with LC-MS/MS was used to analyze putative tegument-exposed proteins in female and male adult Schistosoma ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 78 publications
6
30
0
Order By: Relevance
“…The molecular mechanisms that support injured axon repair and growth parallel that of synaptic vesicle trafficking and neurotransmitter release within uninjured axons, requiring for SNARE proteins 53, 54 . Sj VAMP2 (v- SNARE) has been identified in the tegument of Schistosoma japonicum in the previous study 42, 43 , and our study confirmed the location of Sj VAMP2 specifically in the tegument apical membrane invaginations and the secretory vesicles in the tegument martrix, which implies the role of SjVAMP2 in the tegument membrane maintenance or repair process.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The molecular mechanisms that support injured axon repair and growth parallel that of synaptic vesicle trafficking and neurotransmitter release within uninjured axons, requiring for SNARE proteins 53, 54 . Sj VAMP2 (v- SNARE) has been identified in the tegument of Schistosoma japonicum in the previous study 42, 43 , and our study confirmed the location of Sj VAMP2 specifically in the tegument apical membrane invaginations and the secretory vesicles in the tegument martrix, which implies the role of SjVAMP2 in the tegument membrane maintenance or repair process.…”
Section: Discussionsupporting
confidence: 88%
“…japonicum (hereafter SjVAMP2 ) 41, 42 . Our research group cloned this gene and showed that SjVAMP2 was primarily expressed in the tegument of schistosomes; in addition, its transcripts were highly expressed in 42-day female worms 43 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on tegument proteins also identified several molecules that successfully induced protective immune responses against schistosome infections, such as Sj23, Sm21.6, and Sm29 [3537]. Using the antibody raised against rSjTOR-ed1, we found that SjTOR was mainly distributed in the tegument membrane of S. japonicum and also located in the head of the cercaria and the tegument of miracidia matured in the eggs, with the former supported by a previous proteomics study on tegumental surface proteins of S. japonicum in our laboratory [21]. Therefore, we speculated that SjTOR might be a good vaccine candidate antigen like SmTOR which is a tegument membrane protein and is expressed highly in cercariae [13].…”
Section: Discussionsupporting
confidence: 76%
“…TOR in S. japonicum was first found by Liu et al [20] in cercariae, schistosomula, and adult worms. TOR was also identified in a proteomics study of tegument surface proteins of S. japonicum in our laboratory [21], although no further studies on SjTOR have yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Sjda was not expressed in the male parasites (Figure 7B). Previous studies have shown that the teguments of male and female parasites are structurally different, and the surfaces of male schistosomes are coated with an increased number of sugar components compared to those of female parasites [21]. These findings indicate that male and female parasites possess different arsenals for the resistance of host immune expulsion.…”
Section: Discussionmentioning
confidence: 99%